Chymotrypsin attenuates adjuvant-induced arthritis by downregulating TLR4, NF-κB, MMP-1, TNF-α, IL-1β, and IL-6 expression in Sprague–Dawley rats. (2nd November 2022) - Li, Jianqiang; Wang, Linlin; Zeng, Guangting; Li, Huilan; Luo, Jia; Tian, Qijun; Zhang, Zanling
Abstract: Objective: Rheumatoid arthritis (RA) is mainly characterized by synovial hyperplasia, angiogenesis, inflammatory cells infiltration. Chymotrypsin is a proteolytic enzyme with anti-inflammatory effects. The current project was intended to test the efficacy and mechanism of chymotrypsin in adjuvant-induced arthritis (AIA) rats to provide an experimental basis for the clinical application of chymotrypsin. Methods: Sprague–Dawley rats were injected with complete Freund's adjuvant (CFA) in the hind left paw pad to establish an AIA model. Forty rats were randomly divided into five groups ( n  = 8): blank; CFA model (model); low-dose chymotrypsin (CLD), 0.53 mg/kg; high-dose chymotrypsin (CHD), 1.06 mg/kg; piroxicam, 10 mg/kg. The treatments were performed in the subplantar region of the left hind paw from Day 8 (D8) to Day 28 after adjuvant injection. The body weight, paw diameter, swelling degree of paw, and arthritic score were measured on D0, D7, D14, D21, and D28. All animals were sacrificed on D29. Subsequently, the synovial tissue of the ankle joint of the rats was stained with HE to generate pathological sections for observation of the pathological changes of synovial tissue from the ankle joint. The protein levels of MMP-1, TNF-α, IL-1β, and IL-6 in the rats' serum were determined by ELISA. Western blotting was used to detect the protein expression of TLR4 and NF-κB in the rat ankle tissue. The mRNA expression of TLR4, NF-κB, IL-1β, IL-6, and TNF-α in synovial tissue of the ankle joint was detected by RT-qPCR. Results: The body weight of the rats in each group showed an increasing trend, and there was no significant difference in weight between the groups. CHD and piroxicam suppressed paw swelling and arthritic scores and decreased synovial hyperplasia, inflammatory cell infiltration, pannus formation, and bone destruction. Furthermore, the overproduction of MMP-1, TNF-α, IL-1β, and IL-6 in serum was remarkably attenuated in the chymotrypsin- and piroxicam-treated rats. The protein levels of TLR4 and NF-κB in the synovial tissue of the chymotrypsin group and the piroxicam group were significantly lower than those in the model group. Likewise, the rats treated with chymotrypsin and piroxicam had a substantial decline in the mRNA expression of TLR4, NF-κB, TNF-α, IL-1β, and IL-6 in synovial tissue. Conclusions: Chymotrypsin alleviates the joint damage of AIA rats, probably by reducing the expression of MMP-1, TNF-α, IL-1β, and IL-6 through TLR4/NF-κB signaling pathway.